The FGF1/CPP-C chimera protein protects against intestinal adverse effects of C-ion radiotherapy without exacerbating pancreatic carcinoma. (January 2019) - Kawano, Mitsuko; Miura, Taichi; Fujita, Mayumi; Koike, Sachiko; Imadome, Kaori; Ishikawa, Atsuko; Yasuda, Takeshi; Imamura, Toru; Imai, Takashi; Nakayama, Fumiaki
Graphical abstract: Highlights: C-ion radiotherapy is applied to pancreatic carcinoma in the abdominal cavity. The FGF1/CPP-C chimeric protein has an intracellular signaling mode. FGF1/CPP-C protects against C-ion-induced intestinal damage. FGF1/CPP-C inhibits the proliferation and metastasis of pancreatic carcinoma cells. FGF1/CPP-C may be useful for C-ion radiotherapy against pancreatic cancer. Abstract: Background and purpose: Carbon ion (C-ion) beams are concentrated to irradiate pancreatic carcinoma in the upper abdomen; however, this radiotherapy potentially causes adverse reactions in the gastrointestinal tract. FGF1 is a candidate radioprotector for radiation-induced intestinal damage, but may promote the malignancy of pancreatic cancer. An FGF1/CPP-C chimeric protein was created to enhance the intracellular signaling mode of FGF1 instead of FGFR signaling. The present study investigated the effects of FGF1/CPP-C on the intestinal adverse reactions of C-ion radiotherapy as well as its influence on the malignancy of pancreatic cancer. Materials and methods: FGF1/CPP-C was administered intraperitoneally to BALB/c mice without heparin 12 h before total body irradiation (TBI) with low-LET C-ion (17 keV/μm) at 6–8 Gy. Several radioprotective effects were examined in the jejunum. The invasion and migration of the human pancreatic carcinoma cell lines MIAPaCa-2 and PANC-1 were assessed using Boyden chambers after cultures with FGF1/CPP-C. Results: The FGF1/CPP-C treatment promoted crypt survival after C-ion irradiation at 7–8 Gy significantly more than the FGF1 treatment. FGF1/CPP-C also inhibited C-ion radiotherapy-induced apoptosis and reduced γH2AX foci in crypt cells more than FGF1. However, FGF1/CPP-C inhibited the downstream signaling pathways of FGFRs and suppressed the activation of cell-cycle regulatory molecules in the intestine until 4 h after TBI. Furthermore, IEC6 cells were arrested in G2M after cultures with FGF1/CPP-C or FGF1, suggesting that DNA repair after irradiation is promoted by FGF1/CPP-C-induced G2M arrest. In contrast, FGF1/CPP-C appeared to be internalized into MIAPaCa-2 and PANC-1 cells more efficiently than FGF1. Therefore, FGF1/CPP-C reduced the in vitro proliferation, invasion, and migration of MIAPaCa-2 and PANC-1 cells significantly more than FGF1 through the cellular internalization of FGF1. Conclusion: These results suggest that the intracellular signaling mode of FGF1/CPP-C attenuates the intestinal adverse effects of C-ion radiotherapy without enhancing the malignancy of pancreatic carcinoma.